Iron Deficiency, An Independent Risk Factor for Isolated Hypothyroxinemia in Pregnant and Nonpregnant Women of Childbearing Age in China - Yu, Xiaohui; Shan, Zhongyan; Li, Chenyan; Mao, Jinyuan; Wang, Weiwei; Xie, Xiaochen; Liu, Aihua; Teng, Xiaochun; Zhou, Weiwei; Li, Chenyang; Xu, Bin; Bi, Lihua; et al. (The journal of clinical endocrinology and metabolism, 2015)
Context:Isolated hypothyroxinemia during early pregnancy may irreversibly damage the neurodevelopment of offspring. However, the causes are not well clarified.Objective:To explore the association of iron deficiency (ID) with hypothyroid function of women in early pregnancy and nonpregnant women.Design:A total of 7953 pregnant women of ≤ 12 weeks gestation and 2000 childbearing-aged women were recruited. A subpopulation including 3340 pregnant women and 1052 nonpregnant women with sufficient iodine intake and negative thyroid peroxidase antibody were studied. Mild and severe cases of hypothyroxinemia were defined as free T4 levels below the 10th percentile and the 5th percentile, respectively, with normal TSH. Total body iron, serum ferritin, and serum transferrin receptor were used as indicators for iron nutrition.Results:Serum free T4 levels were significantly lower in both pregnant and nonpregnant women with ID compared with the corresponding groups without ID (both P < .05). The prevalence of mild and severe hypothyroxinemia was markedly higher in women with ID than those without, in both pregnant and nonpregnant women (all P < .01). Logistic regression indicated that ID was an independent risk factor for both mild and severe hypothyroxinemia in pregnancy (odds ratio [OR] = 2.440, 95% confidence interval [CI]: 1.324–4.496, P = .004; and OR = 3.278, 95% CI: 1.443–7.446, P = .005, respectively) and nonpregnancy (OR = 2.662, 95% CI: 1.330–5.329, P = .006; and OR = 3.254, 95% CI: 1.375–7.700, P = .007, respectively).Conclusions:An association between ID and isolated hypothyroxinemia was found in both pregnant and nonpregnant childbearing-aged women, independent of the effects of iodine and thyroid autoimmunity. We speculate that ID may be a pathogenic factor for hypothyroxinemia, even in pregnant women during the first trimester.